Comparaison de differents algorithmes de plasticite dans I' analyse non lineaire des structures de poutres 3D - Guo, Ying Qiao; Shakourzadeh, Hossein (European Journal of Computational Mechanics, 1997)
This paper concerns the presentation and the comparaison of different methods of plasticity of 3D beam structures. The method of progressive plastification is based on the plasticity equations in termes of stresses ; the method of global plastification is based on the plasticity equations in termes of internal forces. The integration of plasticity is carried out with different explicit or implicit schemes. The integrated (total) constitutive law based on the deformation theory of plasticity is also used. The comparaison of the two types of plastification (progressive and global) combined with different integration schemes is the objectif of this paper. The numerical results of our e/asto-plastic beam model are compared with the results of shell models and experiments. This comparaison shows the efficiency and performance of each modele.